Gynecological malignancies at tertiary care hospital, Pakistan: A five-year review - Wasim, Tayyiba (Pak J Med Sci, 2021)
BACKGROUND & OBJECTIVE: Gynecological malignancies are important cause of female morbidity and mortality. They pose significant burden on health resources in low middle-income countries. Data on presentation and risk factors can help in early identification and reduce this burden. Our objective was to evaluate frequency, stage of presentation and risk factors of gynecological malignancies in a tertiary care setting. METHODS: It was cross sectional study done in Gynecology Department, Services Institute of Medical Sciences, Services Hospital, Lahore from January 2015- December 2019. The records of the patients were retrospectively reviewed to include all cases of gynecologic malignancies. Demographic information, frequency, risk factors, symptoms, grade and stage of tumor was collected. RESULTS: There were 122 patients diagnosed with gynecological malignancy during the study period. Ovarian cancer was seen in 60 (49.18%) patients followed by cervical cancer in 29(23.7%), endometrial cancer 27(22.1%) and vulva 06(4.9%). Mean age for all cancers was 51±12.7 to 55±9.3 except cervical cancer which was seen in 43±8.9 years. Patients with ovarian cancer had significantly more hypertension and diabetes (p<0.05). Heavy menstrual bleeding and postmenopausal bleeding was significantly seen in patients of endometrial and cervical cancer (p<0.05). Abdominal symptoms of pain, mass and distension were seen in patients with ovarian cancer (p<0.05). Majority patients presented in advanced stage. Among ovarian cancer, 52/60(86.6%) were epithelial in origin while 25(86.2%) cervical cancer and all vulva cancers were squamous cell carcinoma. CONCLUSION: Ovarian cancer was commonest gynecological malignancy followed by cervical cancer. Late presentation with advanced stage was seen in majority of all cancers.